Analisis Penambahan Jumlah Tenaga Kerja dalam Meningkatkan Pendapatan pada Mie Ayam Baso H. Lili Karawang - Syifa Aulia Dewi; Dedi Mulyadi; Santi Pertiwi Hari Sandi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Revenue is the revenue earned through the results of economic activities related to the sales activities of production factors owned by the company. As known in the theory of production factors, the quantity of output associated with income directly depends on the amount of labor owned. In increasing production supported by efficient resources and running according to the system, appropriate income can be obtained from the level of production. Theoretically, a positive contribution of labor to the increase of business income can occur, especially by involving a large number of workers. This study was conducted to analyze the additional number of workers in increasing revenue at Baso H. Lili Chicken Noodle in Karawang. The type used in this research is descriptive quantitative. The results of this study indicate that Mie Ayam Baso H. Lili Karawang has experienced an increase in labor since the beginning of the business until now, initially only having 3 workers per branch as of 2005, but currently in 2023 it has approximately 7 to 15 workers in each branch. After the additional workforce, H. Lili Karawang’s Baso Chicken Noodle business experienced an increase in income generated with an average of IDR Rp 588.858.818 or the same as around 408%.